Kinerja Aparatur Sipil Negara Dalam Pelayanan Publik di Kantor Camat Botumoito Kabupaten Boalemo - Nihali, Hermanto; Tahir, Arifin; Hamim, Udin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
In the implementation of public services in Indonesia, there are still many irregularities, both at the central and regional levels. The aim of this research is to find out how the State Civil Apparatus performs in public services at the Botumoito Subdistrict Office, Boalemo Regency and what factors can influence it. The research method used in this research is a qualitative descriptive approach. Based on the research results, it shows that the performance of the State Civil Apparatus in public services at the Botumoito Subdistrict Office in terms of quantity, timeliness and ability to work together has shown good results, but in terms of quality it still needs to be improved. Furthermore, looking at the factors that influence the performance of State Civil Apparatus in public services at the Botumoito Sub-District Office, Boalemo Regency, in terms of leadership and teams, they can be factors that encourage the quality of performance of officials in this agency, but individual, system and contextual factors are inhibiting factors.